Georgeiella, a new name for the louse genus Hopkinsiella Clay and Meinertzhagen, 1939 (Phthiraptera, Philopteridae), junior homonym of Hopkinsiella Baba, 1938 (Opisthobranchia, Goniodorididae) - Valim, Michel P.; Palma, Ricardo L. (Zootaxa, 2011)
Clay and Meinertzhagen (1939) described the genus Hopkinsiella to accommodate one new species of louse found on the Kikuyu white-headed wood-hoopoe—Phoeniculus bollei jacksoni (Sharpe, 1890)—of the bird family Phoeniculidae. Tendeiro (1957) described a second species of Hopkinsiella, parasitic on a bird species of the same family. Subsequently, Tendeiro (1961) described one more species and reviewed all the species included in the genus. We have found that the name Hopkinsiella Clay & Meinertzhagen, 1939 is preoccupied by Hopkinsiella Baba, 1938, a genus of nudibranchs – marine gastropod molluscs of the order Opisthobranchia (Baba, 1938).